Do Indonesian Islamic Microfinance Institutions Need Lender of the Last Resort? - Mawardi, Imron; Widiastuti, Tika; Al Mustofa, Muhammad Ubaidillah; Prasetyo, Ari (Universitas Negeri Surabaya, 2020)
Liquidity risk is one of significant risk managed by financial intermediaries including Islamic Microfinance Institutions (IMFIs). The financial intermediaries accept short-term deposits and disburse these deposits in the form of long-term loans. This situation makes IMFI desperately need a lender of last resort (LOLR). Nevertheless, there has been no formal LOLR for Indonesian IMFIs. This study intends to construct the LOLR model for IMFI in Indonesia. This qualitative study applies a case study analysis. This study's subjects are IMFIs in East Java Province that was selected purposively with thirty managers as the key informants. Research findings show that the best model of LOLR is developing a secondary cooperative since the majority form of IMFIs in Indonesia are cooperative entities. With all members of a secondary cooperative deposit for reserve requirements, they can place excess liquidity in the secondary cooperative and ask for financial support.